Treatment journey of spinal cord stimulation surgery: an interpretative phenomenological analysis - Turner, Anna (2012)
Introduction: This thesis explored Chronic Neuropathic Pain (CNP) patients' experiences of the treatment journey of Spinal Cord Stimulation (SCS) surgery, considering life prior to, and after the surgery. Previous SCS literature has predominantly focused on technology, SCS efficacy, and the role of psychological factors in SCS patient selection and outcomes. Whilst research highlights SCS as an effective treatment for various CNP conditions, it predominantly employs quantitative outcome measures, thereby reducing the depth of information yielded about the experience of SCS surgery and patient satisfaction. There is a dearth of in-depth understanding of the lived experience of the SCS surgery treatment journey.